Un feuillet inédit du Martyre d'Apa Nahroou - Lucchesi, Enzo (Analecta Bollandiana, 2006)
Edition and translation of a Sahidic folio of the Martyrdom of Nahrow, to be added to nine others, previously known, of the same codex.